Influence of solution-precursor plasma spray (SPPS) processing parameters on the mechanical and thermodynamic properties of 8 YSZ. Issue 7 (May 2018) - Khan, Matiullah; Hu, Ningning; Zhenhua, Lan; Wang, Yongzhe; Yi, Zeng
Abstract: 8 mol% yttria stabilized zirconia (8YSZ) coatings are prepared by solution precursor plasma spray (SPPS) technique under different spray conditions. Phase analysis is performed using X-ray diffraction (XRD) and Electron back scattered diffraction (EBSD) techniques. Irrespective of the processing conditions and the heat treatment temperatures, all samples displayed cubic and tetragonal zirconia phases. Vertical and horizontal cracks appeared in the microstructural analysis of the coatings. Coating prepared under spray conditions having 40 mm distance between the spray gun and the sample exhibit high hardness, both at 0 h and 10 h heat treatment holding time. To explore the suitability of the coatings for the heat insulating applications, the thermal diffusivity and thermal conductivity are calculated. The coating with 42 mm distance between the spray gun and the sample displayed lowest thermal conductivity from 400 to 1200 ℃.